New microbe genomic variants in patients fecal community following surgical disruption of the upper human gastrointestinal tract. (December 2018) - Kumar, Ranjit; Grams, Jayleen; Chu, Daniel I.; Crossman, David K.; Stahl, Richard; Eipers, Peter; Goldsmith, Kelly; Crowley, Michael; Lefkowitz, Elliot J.; Morrow, Casey D.
Abstract: Recent studies have shown that microbe strains in normal individuals fecal microbe community are relatively stable over time. Given the role the gut microbe community plays in human health, it is important to understand if disruption of the gastrointestinal tract environment results in emergence of new genomic variants. To address this, we have used a new technique called Window-based single nucleotide similarity (WSS) to analyze the impact of several surgical procedures of the human gastrointestinal tract on the stability of the fecal microbes. Previously, we established a WSS boundary score cutoff to determine if microbe genomic variants were similar. Based on analysis of normal individuals from the Human Microbiome Project, 93% of microbes in paired fecal samples up to 1 year apart were above the cutoff, indicating similar (stable) microbes. For the current study, we analyzed fecal samples from 18 patients undergoing Roux-en-Y gastric bypass (RYGB) or 6 patients undergoing gastric sleeve for extreme obesity. From comparison of the pre-RYGB versus 1–2 year post RYGB samples from the same patients, 65% of the WSS were above the boundary cutoff, while for pre versus 1–2 year samples post surgery for patients undergoing sleeve gastrectomy, 75% of the WSS were above the cutoff. In contrast, analysis of fecal samples from 5 patients pre and post removal of segments of the sigmoid colon revealed that 97% of WSS scores were above the cutoff. Our study establishes emergence of new microbe genomic variants in the fecal community following alteration of the upper gastrointestinal environment.